2021
DOI: 10.1088/1755-1315/930/1/012081
|View full text |Cite
|
Sign up to set email alerts
|

Liquefaction Vulnerability Analysis using N-SPT Value and Grain Size Analysis on Gumbasa Irrigation Canal in the Post-Disaster Petobo Area, Sulawesi

Abstract: Strong earthquakes occurred in Central Sulawesi, Indonesia, in late 2018, causing an inheritance disaster, soil liquefaction on Gumbasa Irrigation Canal at Petobo, Sulawesi. Soil liquefaction is a phenomenon of a decreasing soil bearing capacity triggered by strong vibrations in certain soil conditions. It immediately changes the soil characteristic from solid to liquid. Liquefaction vulnerability analysis was done using Idriss-Boulanger’s simplified procedure based on SPT value in several spots. The Petobo li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
(11 reference statements)
1
8
0
Order By: Relevance
“…If the CSR value of any soil deposit is greater than its CRR value, the soil is vulnerable to liquefaction. To get the value of CRR, the equation ( 10) to (13)…”
Section: Liquefaction Vulnerability Analysismentioning
confidence: 99%
“…If the CSR value of any soil deposit is greater than its CRR value, the soil is vulnerable to liquefaction. To get the value of CRR, the equation ( 10) to (13)…”
Section: Liquefaction Vulnerability Analysismentioning
confidence: 99%
“…Previous studies on several segments of irrigation canals affected by liquefaction concluded that factors such as geological site conditions, amplitude, moment magnitude, groundwater table, and soil properties significantly affect liquefaction susceptibility. Petobo and Jono Oge at the downstream of the Sibowi segment irrigation canals tend to have shallow groundwater levels between 1.0 meter to 3.0 meters, with the dominant soil condition being sand from alluvial deposits, and this area has the potential to experience liquefaction at depths between 6-10 m with peak soil acceleration (PGA) occurring at 0.25 g in the Petobo area and 0.4 g in the Jono Oge area [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, knowledge of the liquefaction potential of alluvial deposits is necessary to reduce the risk associated with earthquake-induced liquefaction phenomena in Palu City. Some previous studies have been conducted to analyze liquefaction phenomena, especially in flow liquefaction areas using SPT [3,4] and Vs methods [5]. This paper presents the results of liquefaction potential analysis based on the CPT method in some locations around the city where sand boiling occurred during the 2018 earthquake.…”
Section: Introductionmentioning
confidence: 99%